the alternate method to find the derivative of the function is the limit form.

**By limit process, the derivative of a function f(x) is :-**

**f'(x) = lim h --> 0 [{f(x+h) - f(x)}/h]**

Now, the given function is :-

f(x) = 1/(x-1)

thus, f'(x) = lim h --> 0 [{(1/(x+h-1)) - (1/(x-1))}/h]

or, f'x) = lim h --> 0 [{(x-1) - (x+h-1)}/{h(x-1)*(x+h-1)}]

or, f'(x) = lim h --> 0 [-h/{h*(x-1)*(x+h-1)}] = -1/{(x-1)*(x+h-1)}

putting the value of h = 0 in the above expression we get

f'(x) = -1/{(x-1)^2)}

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now